Sistem Informasi Penjadwalan Maintenance Alat Kesehatan Berbasis Desktop Menggunakan Metode Rapid Application Development - Roziah Roziah; Hery Sunandar; Hukendik Hutabarat (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
The medical equipment Maintenance scheduling process at the Hospital Facilities Maintenance Unit (IPSRS) of RSUP H. Adam Malik Medan still faces several problems, including unintegrated schedule management, relatively slow data retrieval, and manual report preparation. This study aims to design a desktop-based Medical Equipment Maintenance Scheduling Information System using the Rapid Application Development (RAD) method. The system was developed as a desktop application using Visual Basic .NET and SQLite with system modeling based on the Unified Modeling Language (UML). Research data were obtained through observation, interviews, and documentation, with observations conducted on 50 medical equipment Maintenance history records. The system provides 9 main functional groups, including login and access rights, dashboard, medical equipment data management, technician data management, Maintenance scheduling, Maintenance history, notifications, reporting, and logout. Testing was conducted using Black Box Testing on 28 test cases, and all test cases obtained valid results, with a 100% success rate (28/28). These results indicate that all main system functions operated according to the functional requirements and supported a more structured medical equipment Maintenance management process.